The concept of leadership in Islam : a special reference to Ibn Khaldun's Muqaddimah - Ogunbado, Ahamad Faosiy (International Institute of Islamic Thought and Civilization, International Islamic University Malaysia, 2012)
This study concentrates on the concept of leadership from the Islamic perspective in particular and from the Western worldview in general. From the Islamic perspective, the thesis tries to locate the concept as it is found in the Qur'Én, the Sunnah and other sources of Islamic heritage, with special focus on Ibn KhaldËn's academic work entitled the Muqaddimah. The objective of this research is to find how leadership should be practiced as it is explained in our references (the Qur'Én and the Sunnah). It also sets to find possible solutions to the leadership predicament that confronts contemporary Muslim communities. The study uses the qualitative method: a descriptive exploration of leadership types and styles as a phenomenon which has gained momentum as a mode of enquiry for research findings. The research reveals that Muslim nations suffer from poor leadership due to the lack of effective policy-making, of equitable distribution of wealth and above all, high levels of non-transparency in governance. It suggests that implementing Ibn KhaldËn's views on leadership can provide practical solutions for problems of leadership which Muslim nations are experiencing. The research also finds that servant, transformational and charismatic types of leadership, which are recently discovered concepts in contemporary studies, have long been part and parcel of Islamic leadership since its inception in Madinah 15 centuries ago.